OPTIMAL DESIGN OF FLEXIBLE SHALLOW SHELLS ON ELASTIC FOUNDATION - Stupishin, Leonid Yulianovich; Kolesnikov, Alexandr Georgiyevich; Nikitin, Konstantin Evgenyevich (Journal of Applied Engineering Science, 2017)
This paper contains analysis of optimal forms of a geometric nonlinear (flexible) shallow shells based on an elastic foundation. Rise of arch in the center of the shell, width, length and type of support are given. The design variable is taken to be the thickness of the shallow shell, the form of the middle surface forming and the characteristic of elastic foundations. Critical force coefficient and stress of shells are calculated by Bubnov-Galerkin.